Turning Peptide Ligands into Small‐Molecule Inhibitors of Protein–Protein Interactions. Issue 13 (23rd July 2015) - Hashimoto, Chie; Eichler, Jutta
<x xml:space="preserve">Abstract</x> Proline makeover: Truncation and extensive chemical modification of a peptide ligand yielded a biologically active, cell‐permeable, peptidomimetic, small‐molecule inhibitor of a protein–protein interaction. A key step in this transformation was the replacement of a tetraproline motif by two conformationally constrained diproline units that retain the molecule's PPII helix.